(untitled) (International relations and international law Journal, 2016)
Millennium Italian foreign policy orientation has undergone significant changes. If until recently the priority of Italian foreign policy was the Mediterranean region, in the new millennium, there was a shift in emphasis – the integration and interaction of Italy with the EU institutions has been central to the foreign policy of Italy. Mediterranean foreign policy orientation has led to self-elimination of Italy from important European issues to deliberate marginalization of countries in Europe. Italy is one of the regular participants in the political activities of the European Union. In this article is described the interaction of Italy with the EU, particularly such issues as the Italian presidency in the EU in 2003 and the relations between EU and Italy from the beginning. Furthermore, were marked the achievements of Italy during the presidency in 2014, for six month.